Metabolic dysfunction-associated steatotic liver disease: ferroptosis related mechanisms and potential drugs - Zhu, Baoqiang; Wei, Yuankui; Zhang, Mingming; Yang, Shiyu; Tong, Rongsheng; Li, Wenyuan; Long, Enwu (Frontiers in Pharmacology, 2023)
Metabolic dysfunction-associated steatotic liver disease (MASLD) is considered a "multisystem" disease that simultaneously suffers from metabolic diseases and hepatic steatosis. Some may develop into liver fibrosis, cirrhosis, and even hepatocellular carcinoma. Given the close connection between metabolic diseases and fatty liver, it is urgent to identify drugs that can control metabolic diseases and fatty liver as a whole and delay disease progression. Ferroptosis, characterized by iron overload and lipid peroxidation resulting from abnormal iron metabolism, is a programmed cell death mechanism. It is an important pathogenic mechanism in metabolic diseases or Metabolic Dysfunction-associated Fatty Liver Disease